Context and perceptual asymmetry effects on the mismatch negativity (MMNm) to speech sounds: an MEG study. Issue 5 (28th May 2019) - Højlund, Andreas; Gebauer, Line; McGregor, William B.; Wallentin, Mikkel
ABSTRACT: The mismatch negativity (MMN) of the auditory ERP/ERF has been shown to be sensitive to both phonetic and phonological contrasts. However, potential asymmetry effects and effects of the immediate phonetic contexts on this neural sensitivity are understudied phenomena. Using magnetoencephalography (MEG), we attempted to address this lacuna by investigating native Danish listeners' MMNm to the phonological contrast between the consonants /t/ and /d/ in two different phonetic contexts in Danish: one word-initial, preserving the contrast's phonemic status, and another word-final, neutralising it. We found no support for effects of the immediate phonetic context on the MMNm. However, we observed an asymmetry effect for the phonological contrast: Hearing [t] among [d]s elicited a significantly stronger MMNm than hearing [d] among [t]s. This asymmetry effect was mirrored in a behavioural oddball-detection task showing reduced sensitivity for hearing [d] among [t]s. We discuss both psychoacoustic aspects and phonological underspecification as potential explanations.